THE ROLE OF MARRIAGE COUNSELING IN STRENGTHENING MUSLIM FAMILY RESILIENCE: A FIQH MUNAKAHAT PERSPECTIVE - Mansur, Rahmat (Al-Maslahah : Jurnal Ilmu Syariah, 2024)
Marriage in Islam is not just a bond between two individuals, but also a form of worship that has legal and social consequences. But as the times progress, many Muslim couples face challenges in their married lives and often end in divorce. One of the solutions that can be applied to maintain the integrity of the household is through fiqh munaqahat-based marriage consultation. This study analyzes the role and function of marriage consultation in the perspective of fiqh munaqahat and its implications for the resilience of Muslim families. Using a descriptive-qualitative approach, this study examines the urgency of marriage counseling in helping couples understand their rights and obligations, resolve domestic conflicts, and prevent divorce. The results of the study show that marriage consultation contributes to increasing the mental readiness of couples, strengthening communication, and providing solutions based on Islamic sharia in dealing with various household problems. Therefore, further efforts are needed to increase public awareness of the importance of marriage consultation and strengthen institutional support in the implementation of this program.